Mitochondrial gene cytochrome c oxidase I (CO1) used for molecular identification of Bactrocera zonata in Pakistan - Amad, Ikrma; Hafeez, Faisal; Khan, Muhammad Asaf; Nahid, Nazia; Javed, Muhammad Rizwan; Shaheen, Shabnum; Farooq, Muhammad; Khan, Aqib Zafar; Hussain, Khadim (Cellular and Molecular Biology, 2019)
Bactrocera zonata is fruit pest mostly attacked on peach and cause heavy destruction in production of peach fruits by sucking their juice. For their management, we start to detect them on basis of their molecular characterization. As mitochondrial genome encodes a gene COI used as biomarker for identification of eukaryotes including insects. In present study, we amplified COI gene and cloned into pTZ57R/T vector (Fermentas). Cloned gene was confirmed through restriction analysis and sequenced through its entirety on both strands from Macrogen (South Korea) by Sanger sequencing method. Different computational tools were utilized for comparative analysis of sequence with other related sequences retrieved from databases. Related species were identified through phylogenetic analysis using Mega 7 tool. Pairwise sequence alignment showed the sequence identity about 96% with Bactrocera zonata. By identifying the pests with more authentic molecular biomarker may help the research to control them more effectively in future.